Determining the Quality of Earthquake Resistant House Buildings Using Simple Additive Weighting (Saw) and Technique For Order Of Preference By Similarity To Ideal Solution (Topsis) - Burhanuddin Burhanuddin; Bakhtiar; Emi Maulani; Edi Yusuf (Multica Science and Technology (ACCREDITED-SINTA 5), 2024)
This research aims to evaluate the quality of house buildings using the Simple Additive Weighting (SAW) model and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). This research uses six main criteria to assess building quality: Material strength, structural design, foundation, construction technology, construction quality, construction costs. With these six variables in determining the evaluation of house building materials. Determining the final ranking of these alternatives is based on their proximity to the ideal solution. Type A House, Type B House, Type C House, Type D House, Type E House and the weight value for each house C1 = 0.2; C2 = 0.1 ; C3 = 0.15 ; C = 0.20 ; C = 0.15; C = 0.2%. The ranking results for Type A Houses were 0.871, Type B Houses 0.874, Type C Houses 0.813, Type D Houses 0.976 and Type E Houses 0.959. The largest value is in Type D House 0.976 so the alternative Type D House 0.976 is the alternative chosen as the best alternative. Meanwhile, the ranking results for the topsis model for Type A Houses are 0.5423, Type B Houses are 0.5302, Type C Houses are 0.2709, Type D Houses are 0.8515 and Type E Houses are 0.959. The largest value is for Type D House 0.976 so that the Type E House alternative 0.8227 is the alternative chosen as the best alternative for Type E house. The research results show that the combination of the SAW and TOPSIS methods is effective in providing a comprehensive and objective evaluation of the quality of earthquake resistant house buildings. . The results of this research can be applied practically in the construction industry to improve the quality of earthquake-resistant house buildings, helping make more accurate and objective decisions.